Proses Pemecahan Masalah Matematika High Order Thinking Skills Siswa SMA Materi Trigonometri - Tutik Andayani; Yusuf Fuad; Endah Budi Rahaju (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to describe the problem solving process of students with high, medium and low mathematics abilities in solving trigonometry HOTS problems. This research is a descriptive research with a qualitative approach. The research subjects are students of class XI SMA Negeri 1 Driyorejo Gresik, consisting of 36 students who have been given TKM and TPM. Then 3 students with different categories with unique answers were selected. The instrument test was given to XI grade students of SMA Wijaya Putra Surabaya consisting of 30 students. Analysis of the instrument test using Pearson product moment and Cronbach alpha with SPSS 22.0, showed that both instruments were categorized as valid, reliable, significant easy and good differentiation. Data were collected by giving TKM, TPM and interviews. The results showed that the three students understood the problem by rereading the problem, separating the notes on the important points of the problem and identifying the conditions that link the two using the concept of triangle building; BMT and BMS students used the strategy of making drawings and reverse solving, while BMR students determined the wrong solution strategy; BMT and BMS students performed the necessary calculations or solution steps in detail, while BMR subjects had difficulty performing the necessary calculations or steps; BMT students wrote the answer correctly, then rechecked the answer, while BMS and BMR students made the wrong answer conclusion and did not recheck the suitability of the calculation of the length of the sides with the triangle conditions requested by the problem.